Instagram's Role in Inducing Event-Related Social Anxiety for Public Engagement - Helen Fransisca; Rizaldi Parani (LONTAR: Jurnal Ilmu Komunikasi, 2023)
This study aims to illustrate the social anxiety occurring on the Instagram, which creates social influence among individuals regarding entertainment events. This is closely related to the desire of community members to attend Coldplay concerts in Indonesia and neighbouring countries such as Malaysia, the Philippines, Singapore, and Thailand. Therefore, the research question raised is "How can the use of Instagram in creating social anxiety in organizing live events affects the public interest?" The approach used in this study is a qualitative approach with a phenomenological research method. The unit of analysis used is individuals with purposive sampling technique. Data collection was carried out through semi-structured in-depth interviews and relevant literature studies. The theory used in this study is the Uses and Gratification theory because users are active audiences who interact on Instagram. Additionally, this study also incorporates several related concepts such as Social anxiety, social influence, and New media. The study findings reveal that many Instagram users experience anxiety regarding the one-day Coldplay concert in Indonesia. As a result, many fans are interested in attending Coldplay concerts held in several neighbouring countries of Indonesia. This indicates that content on Instagram plays a significant role in shaping community interest.